The Impact of Air Pollution on the Prevalence of Acute Respiratory Infections among Outdoor Workers - Sumiyati Sumiyati (Al Makki Health Informatics Journal, 2025)
This study aims to examine the impact of ambient air pollution exposure on the prevalence of acute respiratory infections (ARI) among outdoor workers. Given the increasing urban air pollution levels in Indonesia, outdoor laborers such as street vendors, construction workers, and traffic police represent a vulnerable population with prolonged exposure to hazardous air pollutants. A cross-sectional observational study was conducted among 300 outdoor workers in three urban areas with varying pollution levels. Air quality data, including concentrations of particulate matter (PM2.5 and PM10), were obtained from local monitoring stations. Health outcomes were assessed through standardized questionnaires on respiratory symptoms and medical history, alongside clinical examinations conducted by health professionals. Logistic regression analysis was applied to evaluate the association between exposure levels and ARI prevalence, controlling for confounders such as age, smoking habits, and socioeconomic status. The study revealed a significantly higher prevalence of ARI among outdoor workers in high-pollution areas compared to those in lower-pollution regions (37.2% vs. 18.9%; p < 0.01). Logistic regression analysis indicated that exposure to elevated PM2.5 levels was strongly associated with increased risk of ARI (OR = 2.41, 95% CI: 1.52–3.82). Smoking and low socioeconomic status were also identified as contributing risk factors, though air pollution remained the strongest predictor. Air pollution substantially elevates the risk of ARI among outdoor workers. These findings highlight the urgent need for targeted occupational health interventions, improved air quality policies, and the provision of personal protective measures to safeguard vulnerable populations.